2021
DOI: 10.1016/j.phro.2021.07.005
|View full text |Cite
|
Sign up to set email alerts
|

Patient position verification in magnetic-resonance imaging only radiotherapy of anal and rectal cancers

Abstract: Background and Purpose: Magnetic resonance (MR)-only treatment pathways require either the MR-simulation or synthetic-computed tomography (sCT) as an alternative reference image for cone beam computed tomography (CBCT) patient position verification. This study assessed whether using T2 MR or sCT as CBCT reference images introduces systematic registration errors as compared to CT for anal and rectal cancers. Materials and Methods: A total of 32 patients (18 rectum,14 anus) received pre-treatment CT-and T2 MRsim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…Other studies have assessed MRI-CBCT matching using automatic registration algorithms. Edmund et al assessed automatic registration for prostate with a resulting 2 mm difference amongst the matching cohort, while Bird et al, assessed a single observer automatic registration for rectal and anal canal regions [17] , [24] . Bird et al, reported a < 1 mm difference and < 0.4° in automatic registration differences [17] .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Other studies have assessed MRI-CBCT matching using automatic registration algorithms. Edmund et al assessed automatic registration for prostate with a resulting 2 mm difference amongst the matching cohort, while Bird et al, assessed a single observer automatic registration for rectal and anal canal regions [17] , [24] . Bird et al, reported a < 1 mm difference and < 0.4° in automatic registration differences [17] .…”
Section: Discussionmentioning
confidence: 99%
“…Edmund et al assessed automatic registration for prostate with a resulting 2 mm difference amongst the matching cohort, while Bird et al, assessed a single observer automatic registration for rectal and anal canal regions [17] , [24] . Bird et al, reported a < 1 mm difference and < 0.4° in automatic registration differences [17] . While the reported difference was lower for Bird et al, than in this study, the use of automatic registration is not necessarily reflective of clinical practice, as clinical decisions and adjustments to the image matching need to be made for anatomical changes daily, therefore, these studies do not take into account the differences imparted from MRI image interpretation in image guidance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation